The His-tag as a decoy modulating preferred orientation in cryoEM - Bromberg, Raquel; Cai, Kai; Guo, Yirui; Plymire, Daniel; Emde, Tabitha; Puzio, Maciej; Borek, Dominika; Otwinowski, Zbyszek (Frontiers in Molecular Biosciences, 2022)
The His-tag is a widely used affinity tag that facilitates purification by means of affinity chromatography of recombinant proteins for functional and structural studies. We show here that His-tag presence affects how coproheme decarboxylase interacts with the air-water interface during grid preparation for cryoEM. Depending on His-tag presence or absence, we observe significant changes in patterns of preferred orientation. Our analysis of particle orientations suggests that His-tag presence can mask the hydrophobic patches on a protein’s surface that mediate the interactions with the air-water interface, while the hydrophobic linker between a His-tag and the coding sequence of the protein may enhance other interactions with the air-water interface. Our observations suggest that tagging, including rational design of the linkers between an affinity tag and a protein of interest, offer a promising approach to modulating interactions with the air-water interface.